Stretching of polycaprolactone films for tissue engineering - Reddy, K Sangeev (2015)
This project was carried out to achieve two specific aims. The first was to develop and characterise a platform to fabricate polymer thin films through biaxial and uniaxial stretching. The second aim was to fabricate and characterise polymer thin films with improved mechanical properties. Polycaprolactone(PCL) was chosen to be the primary polymer to be used in the fabrication. For this project, PCL Sigma Aldrich, medical-grade PCL(mPCL) and a polymer blend of mPCL and Tricalcium Phosphate(TCP) were used in the fabrication of thin films. The fabrication process of thin films involved cryomilling, polymer extrusion, heat pressing and the drawing of the un-stretched films. Characterisation of the thin films were conducted through tensile tests and differential scanning calorimetry before and after the drawing of films. From the results, it was found that un-stretched PCL Sigma Aldrich films had a strain of around 500% while un-stretched mPCL and mPCL/TCP films had a strain of around 80%. PCL Sigma Aldrich films were successfully drawn biaxially to a draw ratio of 3X3 using a chamber temperature of 55°C that was achieved through a heating element temperature of 280°C. Tensile testing studies showed that the tensile strength of biaxially drawn PCL thin films were threefold stronger than the un-stretched PCL films. mPCL and mPCL/TCP films were not successfully stretched biaxially. Uniaxial stretching for the above mentioned polymers were also carried out but the results were not successful. This project re-emphasised the beauty of polymer thin films wherein the films remain thin while exhibiting strong mechanical properties. Based on the properties of the thin PCL films drawn in this project, biomedical applications such as skin grafts, artificial blood vessels, bone scaffolds and in vivo controlled drug delivery were suggested.